Inhibition of Renal Metabolism. Relative effects of arsenate on sodium, phosphate, and glucose transport by the rabbit proximal tubule. - Brazy, P C (1980)
These studies examine the inhibitory effects of arsenate on the transport of sodium, phosphate, glucose, and para-aminohippurate (PAH) as well as oxidative metabolism by proximal convoluted tubules from the rabbit kidney. Transport rates were measured with radioisotopes in isolated and perfused segments. Metabolic activity was monitored through oxygen-consumption rates and HADH fluorescence in parallel studies in suspensions of cortical tubules. The addition of 1mM arsenate to the perfusate reduced fluid absorption rates from 1.24 +/- 0.17 to 0.66 +/- 0.19 nl/nm.min (P < 0.01) and lumen-to-bath phosphate transport from 9.93 +/- 3.47 to 4.25 +/- 1.08 pmol/mm.min (P < 0.01). Similar concentrations of arsenate reduced glucose transport only slightly from 66.1 +/- 6.0 to 56.8 +/-4 4.6 pmol/mm.min (P < 0.05) and had no effect of PAH secretion. Removing phosphate from the perfusate did not affect the net transport of sodium or glucose. In suspensions of tubules, arsenate increased oxygen consumption rates by 20.5 +/- 2.9% and decreased NADH fluorescence by 10.8 +/- 1.5%. These effects on metabolism were concentration dependent and magnified in the presence of ouabain. The data indicate that arsenate's main effect is to uncouple oxidative phosphorylation, and that graded uncoupling of oxidative metabolism causes graded reductions in the net transport of both sodium and phosphate. Glucose transport is inhibited only slightly and PAH secretion is not affected. Thus, partial as opposed to complete inhibition of metabolism reveals that different relationships exist between net sodium transport and the transport of phosphate, glucose, and PAH by the proximal renal tubule.